Analyzing Learning Strategies of Top-Performing Students in English Speaking Classes at Junior High School in Indonesia - Tikiawati Tikiawati; Siti Drivoka Sulistyaningrum; Dila Anggita (Journal of English Language Studies, 2024)
This research aimed to investigate learning strategies used by Junior High school to enhance English speaking skill, with a particular focus on identifying the dominant strategy. To achieve this, a descriptive qualitative method was used to examine interaction patterns within the classroom. The participants were comprised of 5 at VIII Grade Junior High School students who achieved the highest scores and willingly provided essential data to address the research questions. Data were collected through multiple sources, including transcribed interviews and observation. The results showed that 1) Students improved their accents by rehearsing and mimicking speech sounds, listening to native speakers, engaging with music, watching English flicks, consulting Google Translate, reading English books, singing English songs, swapping written notes, as well as requesting for opportunities to converse with teacher and peers in English. 2) Students frequently asked for guidance from peers on proper sentence construction, practiced speaking regularly, learnt from English movies, and occasionally referenced a dictionary. These observations suggested a dominant use of cognitive learning strategy, characterized by repetition, summarization, and contextual imagery, and driven by students’ personal preferences or available resources. Meanwhile, Socio-Affective strategy, including interaction with others to aid in learning, ranked second, as students actively collaborated with peers. This research could potentially assist teacher in enhancing student speaking skill by gaining insight into learning behaviors and preferences, facilitating the selection of appropriate teaching strategies.